Saliva as a diagnostic tool for glucose estimation in diabetic patients - Deepali Pandey; Poornima Chandra; Prabhakara Somanna; Revathi Sampath; Balaji Pachipulusu (Wolters Kluwer Medknow Publications, 2023)
Background: Diabetes mellitus is a common disease which manifests itself as hyperglycemia. For many years, the question of the presence of glucose in saliva has been a subject of debate and correlation between serum glucose and salivary glucose in diabetics is uncertain. Objectives: The purpose of this study was to estimate salivary glucose concentration and correlate it with serum glucose concentration in diabetics and healthy controls. Materials and Methods: Two milliliters of blood and 2 ml of unstimulated whole saliva were collected from both diabetics and healthy controls. The serum glucose (SeGl) and salivary glucose (SaGl) levels were estimated by using a spectrophotometer. Statistical Analysis: The mean salivary glucose levels between the study and control groups was compared using Mann-Whitney test. Spearman's rank correlation test was done to study the relationship between SeGl and SaGl in both the groups. Simple linear regression analysis was used for predicting serum glucose levels. Results: There was a statistically significant difference in SeGl and SaGl between diabetics and controls. There was a weak correlation between SeGl and SaGl in diabetics and a very weak correlation in SeGl and SaGl in controls, but both were statistically significant. Conclusion: Salivary glucose is an efficient indicator for the presence or absence of diabetes, but it may not be a reliable tool for quantitative estimation of glucose. A reference scale between serum and salivary glucose could not be established due to their weak correlation.